New striatal neurons in a mouse model of progressive striatal degeneration are generated in both the subventricular zone and the striatal parenchyma. - Federico Luzzati (PLoS ONE, 2011)
Acute striatal lesions increase proliferation in the subventricular zone (SVZ) and induce migration of SVZ neuroblasts to the striatum. However, the potential of these cells to replace acutely degenerated neurons is controversial. The possible contribution of parenchymal progenitors to striatal lesion-induced neurogenesis has been poorly explored. Here, we present a detailed investigation of neurogenesis in the striatum of a mouse model showing slow progressive neurodegeneration of striatal neurons, the Creb1(Camkcre4)Crem⁻/⁻ mutant mice (CBCM). By using BrdU time course analyses, intraventricular injections of a cell tracker and 3D reconstructions we showed that neurodegeneration in CBCM mice stimulates the migration of SVZ neuroblasts to the striatum without altering SVZ proliferation. SVZ-neuroblasts migrate as chains through the callosal striatal border and then enter within the striatal parenchyma as individual cells. In addition, a population of clustered neuroblasts showing high turnover rates were observed in the mutant striatum that had not migrated from the SVZ. Clustered neuroblasts might originate within the striatum itself because they are specifically associated with parenchymal proliferating cells showing features of intermediate neuronal progenitors such as clustering, expression of EGF receptor and multiple glial (SOX2, SOX9, BLBP) and neuronal (Dlx, Sp8, and to some extent DCX) markers. Newborn striatal neurons had a short lifespan and did not replace projection neurons nor expressed sets of transcription factors involved in their specification. The differentiation failure of endogenous neuroblasts likely occurred cell autonomously because transplanted wild type embryonic precursors correctly differentiated into striatal projection neurons. Thus, we propose that under progressive degeneration, neither SVZ derived nor intra-striatal generated neurons have the potential to differentiate into striatal projection neurons.